Radicalisation and Counter-Radicalisation in Higher Education. - McGlynn, Catherine (Great Debates in Higher Education Ser., 2018)
This book draws on primaryresearch to present a critical overview of debates about UK university campusesas a location for radicalisation and the impact of counter-radicalisationpolicies. It provides a historical overview and a contemporary assessment ofradicalisation in Universities and covers teaching, student and governanceaspects of HE.